2019
DOI: 10.1038/s41467-019-09251-5
|View full text |Cite
|
Sign up to set email alerts
|

A post-translational modification of human Norovirus capsid protein attenuates glycan binding

Abstract: Attachment of human noroviruses to histo blood group antigens (HBGAs) is essential for infection, but how this binding event promotes the infection of host cells is unknown. Here, we employ protein NMR experiments supported by mass spectrometry and crystallography to study HBGA binding to the P-domain of a prevalent virus strain (GII.4). We report a highly selective transformation of asparagine 373, located in an antigenic loop adjoining the HBGA binding site, into an iso-aspartate residue. This spontaneous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
166
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(181 citation statements)
references
References 75 publications
14
166
1
Order By: Relevance
“…Using a freshly purified sample of NN P dimers we obtained a K D value of 5.6 m m (cf. Figure ), in excellent agreement with the value of 5.5 m m from a competition STD NMR experiment …”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Using a freshly purified sample of NN P dimers we obtained a K D value of 5.6 m m (cf. Figure ), in excellent agreement with the value of 5.5 m m from a competition STD NMR experiment …”
Section: Resultssupporting
confidence: 86%
“…Our experiments show that binding of bile acids to the low‐affinity site and binding of HBGAs to the HBGA site are independent events. Likewise, we have shown that the influence of spontaneous deamidation in the HBGA binding site on the binding affinity for bile acids is negligible. These findings suggest that there is no or very minor cross‐talk between these binding events.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations